Enhanced performance and optimization of a corrugated triple-tube latent heat thermal energy storage unit - Jingmei Yu; Xuefeng Jiang; Xinle Yang; Bingxuan Yu; Songyang Xu (Case Studies in Thermal Engineering, 2025)
To improve the poor heat transfer and uneven melting in conventional triple-tube latent heat thermal energy storage (LHTES) systems, a novel corrugated tube design coupled with V-shaped fins is proposed. Numerical simulations were used to analyze the effects of corrugation number and scaling ratio on thermal performance. Results show that this design reduced the total melting time by 91.4 min (68.95 %) with only a 4.5 % reduction in heat storage capacity (340 kJ). Five corrugations shortened inner phase change material (PCM) melting time by 58.5 min (44.14 %) and outer PCM by 27.76 min (30.35 %). A scaling ratio of 1.2 led to nearly simultaneous melting, reducing the inner-outer melting time gap from 10.35 to 0.85 min. V-shaped fins further enhanced performance. Optimization indicated that longer fins and smaller angles accelerate melting in difficult regions. The optimal configuration (L1 = 16.48 mm; L2 = 35.99 mm; θ1 = 39.25°; θ2 = 43.08°) cut the inner and outer PCM melting times by 50 % and 43.7 %, respectively. This work offers theoretical support for future LHTES designs.